Effect of epigallocatechin gallate, green tea extract and chlorhexidine application on long-term bond strength of self-etch adhesive to dentin. (December 2016) - Gerhardt, K.M.F.; Oliveira, C.A.R.; França, F.M.G.; Basting, R.T.; Turssi, C.P.; Amaral, F.L.B.
Abstract: This study evaluated the effect of dentin pretreatment with metalloproteinase inhibitors on long-term microtensile bond strength (μTBS) of self-etch adhesive (SEA) to dentin. Thirty-two dentin fragments received pretreatments ( n =8): C: control (not treated); GT: 2% green tea extract; CLX: 2% chlorhexidine; EGCG: 2% epigallocatechin gallate. SEAs (Clearfil SE Bond) and resin composite were applied to dentin surface. After 24 h, resin-blocks were cut into sticks submitted to μTBS testing immediately or after 6 months of storage in water. Two-way ANOVA and Tukey test ( α =5%) indicated that CLX group showed μTBS values statistically superior to the other groups at immediate testing, whereas those of EGCG group were the lowest ( p =0.018). After 6 months, a significant increase in μTBS values was observed for all groups, except for CLX ( p =0.018). In conclusion, μTBS increased in dentin pretreatment with EGCG and green tea groups, and in the non-treated group.